ANGI-02. A CRITICAL ROLE FOR LARG IN RhoC MEDIATED GLIOBLASTOMA CELL INVASION. (5th November 2018) - Ding, Zonghui; Dong, Zhiwan; Yang, Yuping; Fortin-Ensign, Shannon; Sabit, Hemragul; Nakada, Mitsutoshi; Ruggieri, Rosamaria; Symons, Marc; Tran, Nhan; Loftus, Joseph
Abstract: Glioblastoma (GBM) is the most common and highly lethal central nervous tumor in adults. A significant hurdle to effective clinical treatment is the aggressive, highly diffuse infiltration of tumor cells into the normal brain parenchyma which makes surgical removal of GBM tumors impossible, increases resistance to chemotherapy and radiation treatment, and ultimately leads to tumor recurrence. A distinguishing feature of the brain parenchyma is the tight extracellular space resulting from the densely packed neurons and glial cells. Invasion of glioblastoma cells into the brain parenchyma is challenged by migration through extracellular spaces that are narrower than the nuclear diameter. In an effort to identify signaling elements involved in cell invasion which requires nuclear squeezing, we examined the role of proteins involved in regulating actomyosin contractility. We demonstrate that siRNA-mediated depletion of the leukemia-associated Rho guanine nucleotide exchange factor (LARG), which was originally identified as a result of chromosomal translocation in acute myeloid leukemia, impaired the nuclear squeezing of glioblastoma cells in vitro and invasion into brain slices ex-vivo . Moreover, depletion of LARG inhibited serum-induced activation of RhoC, but not RhoA. In addition, transwell migration assays with 3-μm pore size filter and matrigel invasion assays demonstrated that RhoC is essential for nuclear squeezing and glioblastoma invasion whereas RhoA is dispensable. Finally, immunohistochemistry analysis demonstrated that the expression of LARG and RhoC increases with glial tumor grade and are highest in glioblastoma and their expression is enriched in the invading cells. Collectively, these results suggest that LARG plays an essential role in glioblastoma cell invasion and may provide new insight into targeting invasive glioblastoma cells.